Conventionally fractionated radiotherapy versus CyberKnife hypofractionated radiotherapy for painful vertebral haemangiomas – A randomized clinical trial. (November 2022) - Miszczyk, Marcin; Napieralska, Aleksandra; Woźniak, Grzegorz; Kraszkiewicz, Małgorzata; Gola, Michał; Kalemba, Michał; Głowacki, Grzegorz; Tomasik, Bartłomiej; Kocot-Kępska, Magdalena; Miszczyk, Leszek
Highlights: Five fractions hypofractionated radiotherapy for painful haemangiomas is safe and effective. The delivery of 25 Gy in 5 fractions is associated with improved subjective pain relief at two years compared to 36 Gy in 18 fractions. Hypofractionation significantly reduces the number of necessary hospital visits and overall treatment time. Abstract: Background and purpose: The outcomes of conventional radiotherapy for painful vertebral haemangiomas have been improved through dose escalation at the expense of overall treatment time. We hypothesized that with the aid of precise hypofractionated radiotherapy, it is possible to safely deliver a similar biological equivalent dose over a significantly shorter course of treatment with a comparable efficacy and safety. Materials and methods: In this prospective, single-institution unblinded randomized clinical trial (NCT02332408) patients with painful vertebral haemangiomas were allocated one-to-one either to 25 Gy delivered in five fractions (CK) or conventionally fractionated radiotherapy up to 36 Gy (conv.). The main endpoint was pain relief at two years, measured on a subjective and numerical scale (NRS). Results: The trial was finished yielding 74 evaluable patients, including 38 in the CK arm. Adverse events were infrequent and the treatment was well tolerated. The overall treatment time was significantly shorter in the CK arm (median of 13 days vs 25 days). At two years, more than half of the patients reported improvement (46; 62.2 %), in 21 cases the pain symptoms were stable (28.4 %), and in seven cases worse (9.5 %). There were significantly more patients reporting improvement in the CK arm (73.7 % vs 50 %; p = 0.036). The median decrease in NRS was 4 (IQR 1–5) or 59 % (IQR 20–86 %), and the difference between arms was not statistically significant. Conclusion: Five fractions hypofractionated radiotherapy for painful vertebral haemangiomas up to a total dose of 25 Gy is a safe treatment modality, significantly shorter compared to conventional fractionation, and possibly more effective.